The structure of profile Russian language teaching in the conditions of level differentiation of subject content (Филологический класс, 2007)
The author reveals her own idea of the structure of teaching the Russian language, which can be a basis for the pattern of multilevel education in profile school. The author characterizes the commonly used textbooks on the Russian language for senior students (basic, profile and advanced levels), recommended by the Ministry of Education RF.